Job satisfaction among quantity surveyors in construction firms - Ong, Chee Ling, 1990-; Norazam Othman, supervisor; Nafisah Abdul Rahiman; Fakulti Alam Bina (2013)
Project Paper (Sarjana Muda Ukur Bahan) - Universiti Teknologi Malaysia, 2013